Finite Element Method-Based Spherical Indentation Analysis of Jute/Sisal/Banana-Polypropylene Fiber-Reinforced Composites - Nitish Kaushik; Ch. Sandeep; P. Jayaraman; J. Justin Maria Hillary; V. P. Srinivasan; M. Abisha Meji (Adsorption Science & Technology)
Material hardness of natural fiber composites depends upon the orientation of fibers, ratio of fiber to matrix, and their mechanical and physical properties. Experimentally finding the material hardness of composites is an involved task. The present work attempts to explore the deformation mechanism of natural fiber composites subjected to post-yield indentation by a spherical indenter through a two-dimensional finite element analysis. In the present work, jute-polypropylene, sisal-polypropylene, and banana-polypropylene composites are considered. The analysis is attempted by varying the properties of Young’s modulus of fiber and matrix, diameter of fiber, and horizontal and vertical center distance between the fibers. The analyses results showed that as the distance between the fiber’s center increases, the bearing load capacity of all composite increases nonlinearly. The jute fiber composite shows predominate load-carrying capacity compared to other composites at all L/D ratios and interference ratios. The influence of subsurface stress in lateral direction is minimal and gets reduced as the distance between the fiber centers increases. The variation in diameter of fiber influences significantly, i.e., beyond the L/D ratio of 1.0; for the same contact load ratio, the bearing area support is double for jute-polypropylene composite compared to sisal-polypropylene composite. Compared to the sisal-polypropylene composite, for the same interference ratio, the load-carrying capacity is two times high for banana-polypropylene composite, whereas four times high for jute-polypropylene composite, but this effect decreases as the L/D ratio decreases. In all the composites, the subsurface stress gets distributed as the L/D ratio increases. The ratio of fibers center distance to diameter of fiber influences marginally on the contact load and contact area and significantly on the contact stress for all the fiber-reinforced composites.